ANALYSIS OF STUDENTS’ MATHEMATICAL COMMUNICATION ABILITY BASED ON SELF-CONFIDENCE AND COGNITIVE STYLE - Baskoro, Jarot Aji; Turmudi, Turmudi; Gozali, Sumanang Muhtar (Jurnal Pendidikan Matematika (JUPITEK), 2024)
Self-confidence and cognitive style are important variables that influence the behavior of students in the academic field, the continued development of academic abilities, how learning is carried out, and how they interact in classroom activities. Learning activities will be expected more effective because all of the learning steps going to be attractive and get to reach the learning achievements if students have good self-confidence. So, all of these things are related to mathematical communication ability. The data on students' mathematical communication ability scores that were influenced by two factors, the level of self-confidence and different cognitive styles, were analyzed by the experimental design carried out in this research was a 3x2 Completely Randomized Factorial Design. The observation data were analyzed statistically with the F-test at a significance level of 5%. From the test of between-subjects effects, the output data was on the ANOVA table. We can get the conclusion that there was factors interaction which can be seen by p-value (Sig.) < α = 0.05, which means rejected H0. There was an effect of interaction between self-confidence with cognitive style significantly to mathematical communication ability